2010
DOI: 10.1590/s0104-11692010000500014
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Type 2 Diabetes Mellitus in Children

Abstract: This study investigates risk factors for type 2 diabetes mellitus in a population of children in public schools, Fortaleza, CE, Brazil. A total of 727 children aged 6 to 11 years old from 12 schools were evaluated between March and June 2008. A form addressing sociodemographic data, body mass index, blood pressure, capillary blood glucose and waist circumference was applied. A total of 54.1% of the children were female, 21.7% were overweight, 6.6% were obese, 27% had central obesity, 6.2% showed altered capill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…In this context, the treatment is long and the prevention of metabolic disorders a public health priority; the change can start in the nursing consultations in the health centers (19) , as well as through health education actions in the schools (20) . It is stressed, however, that in spite of the nurse being fundamental in this process, it is necessary for the actions to be multi-and inter-disciplinary, through teamwork, in which other professionals, such as nutritionists and the psychologists, may also be mediators.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the treatment is long and the prevention of metabolic disorders a public health priority; the change can start in the nursing consultations in the health centers (19) , as well as through health education actions in the schools (20) . It is stressed, however, that in spite of the nurse being fundamental in this process, it is necessary for the actions to be multi-and inter-disciplinary, through teamwork, in which other professionals, such as nutritionists and the psychologists, may also be mediators.…”
Section: Resultsmentioning
confidence: 99%
“…The nurses observed that among children 21.7% were overweight, 27% had abdominal obesity, 17.9% had high blood pressure and 6.2% glucose alterations. (8) In the adolescent population there was high prevalence of a sedentary lifestyle (65.1%) and family history of type 2 diabetes mellitus (51.1%). (9) In adults prevalence was even higher: 47.1% were overweight, 30.7% had abdominal obesity and 70,9% had a sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…The first [12] brought as a factor of risk a family history of type 2 diabetes, high BMI and high blood pressure. On the other hand [13], in line with the first, investigated overweight and high blood pressure; however, it did not investigate family history with DM as a risk factor. Those results corroborate the ones standardized by the American Diabetes Association (ADA) [12].…”
Section: Discussionmentioning
confidence: 99%